Gastrointestinal Autonomic Neuropathy Exacerbates Gut Microbiota Dysbiosis in Adult Patients With Type 2 Diabetes Mellitus - Du, Yuhui; Neng, Qiongli; Li, Yu; Kang, Yongbo; Guo, Liqiong; Huang, Xinwei; Chen, Minghui; Yang, Fan; Hong, Jingan; Zhou, Shuai; Zhao, Jianhua; Yu, Fubing; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The diabetic autonomic neuropathy is one of the most common complications in type 2 diabetes mellitus (T2DM), especially gastrointestinal autonomic neuropathy (GAN), which occurs in up to 75% of patients. The study aimed to investigate the gut microbiota composition, structure, and function in T2DM patients with GAN (T2DM_GAN) and set up a link between gut microbiota and clinical characteristics of patients. Methods DNA was extracted from fecal samples of three groups using the kit method: healthy volunteers (n = 19), the patients with T2DM (n = 76), and T2DM_GAN (n = 27). Sequencing of 16S ribosomal DNA was performed using the MiSeq platform. Results According to the clinical data, higher age, lower triglyceride, and lower body mass index were the main features of patients with T2DM_GAN. The gut microbiota analysis showed that Bacteroidetes, Firmicutes, and Proteobacteria constituted the three dominant phyla in healthy individuals. In addition, the gut microbiota structure and function of T2DM_GAN patients were clearly different from that of T2DM patients. T2DM patients were characterized by Fusobacteria, Fusobacteriia, Fusobacteriales, Fusobacteriaceae, Fusobacterium, Lachnoclostridium, and Fusobacterium_mortiferum. Those gut microbiota may be involved in carotenoid and flavonoid biosyntheses. Relatively, the Gammaproteobacteria, Enterobacteriales, Enterobacteriaceae, Escherichia-Shigella, Megasphaera, Escherichia_coli, and Megasphaera_elsdenii were characteristic in the T2DM_GAN patients. Those may be involved in bacterial invasion of epithelial cells and pathogenic Escherichia coli infection. Conclusions GAN exacerbated gut microbiota dysbiosis in adult patients with T2DM. The findings indicated that phyla Fusobacteria and class Gammaproteobacteria were closely related to the occurrence of T2DM. Especially the latter may promote T2DM_GAN.